1995
DOI: 10.1016/0370-1573(94)00112-g
|View full text |Cite
|
Sign up to set email alerts
|

Antibracket, antifields and gauge-theory quantization

Abstract: The antibracket formalism for gauge theories, at both the classical and quantum level, is reviewed. Gauge transformations and the associated gauge structure are analyzed in detail. The basic concepts involved in the antibracket formalism are elucidated. Gauge-fixing, quantum effects, and anomalies within the field-antifield formalism are developed. The concepts, issues and constructions are illustrated using eight gauge-theory models.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
591
0
5

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 394 publications
(615 citation statements)
references
References 281 publications
5
591
0
5
Order By: Relevance
“…More detailed reviews on the BV scheme, reflecting the point of view of the present authors, can be found in [12,13,14]. Other recommended reading on BV is [15].…”
Section: Batalin-vilkovisky Lagrangian Quantisationmentioning
confidence: 99%
“…More detailed reviews on the BV scheme, reflecting the point of view of the present authors, can be found in [12,13,14]. Other recommended reading on BV is [15].…”
Section: Batalin-vilkovisky Lagrangian Quantisationmentioning
confidence: 99%
“…The gauge structure of a theory is encoded in the BV formalism [21]. For a review, see for example [22,23]. The construction of the classical master equation and the BRST symmetry will be given elsewhere [24].…”
Section: Gauge Symmetriesmentioning
confidence: 99%
“…To derive these conditions, we assume that there is a regularization scheme with the properties of dimensional regularization as used in [13], although we expect the cohomological restrictions to be independent of the regularization method. Notational conventions for the Batalin-Vilkovisky formalism will be those of the reviews [14,15]. The analysis applies to local and rigid symmetries if we understand the master equation to be the generalized master equation discussed in [16].…”
mentioning
confidence: 99%